Socio-Cultural variations in Consumer preferences on Sexual Wellness Products in Urban and Rural Communities: A Comprehensive Analysis - Das, Soumyajit; Narayan, Prachi (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
This study scrutinizes the multifaceted dimensions of sexual wellness, encompassing physical, mental, and social well-being within the sexual paradigm. It investigates the impact of sexual wellness products (SWP) on consumer behaviour, emphasizing divergences in buying patterns between rural and urban societies. Employing the Theory of Planned Behaviour, the study integrates attitudes, subjective norms, perceived behavioural control, and interactive intention to elucidate their collective influence on SWP and utilizing quantitative method. The findings reveal a positive relationship between attitudes and behavioural intentions on SWP, with subjective norms contributing notably to behavioural intentions. The research compares rural and urban consumers having a sample size of 546, that employs a comprehensive structural equation model, revealing intricate interrelationships (χ² = 1852.68, χ²/df = 2.85, CFI = 0.94, GFI = 0.91, TLI = 0.93, RMSEA = 0.078) among various attributes in the sexual wellness product domain, shaping mathematical patterns in consumer behaviour and perceptions. These insights offer actionable guidance for marketers and policymakers to tailor strategies to the distinct characteristics of diverse consumer segments. Urban-rural distinctions in socio-cultural values, access, economic factors, education, and community influences emerge as pivotal drivers shaping consumer behaviour and feelings. Urban environments show greater openness and accessibility, while rural settings, rooted in tradition, face limitations, emphasizing the need for tailored marketing strategies and public health interventions. This study bridges the gap between marketing, public health, and socio-cultural dynamics, offering a data-driven approach to understanding and addressing consumer behavior in the sexual wellness market. It provides theoretical advancements, empirical insights, and practical applications that collectively enhance both academic discourse and real-world strategy development in the field.